Efficient numerical schemes for solving the self‐consistent field equations of flexible–semiflexible diblock copolymers. (10th July 2013) - Liang, Qin; Jiang, Kai; Zhang, Pingwen
Abstract : We present two efficient iterative schemes for solving the self‐consistent field equations of flexible–semiflexible diblock copolymers. One is a semi‐implicit scheme developed by employing asymptotic expansion, and the other is a hybrid scheme combining the robustness of the steepest descent method with the efficiency of the conjugate gradient method. In our position‐one‐dimensional and position‐two‐dimensional numerical experiments, we demonstrate that these schemes are much more efficient than the steepest descent method. Copyright © 2013 John Wiley & Sons, Ltd.